Nutritional Habits According to Gender, Stage of Exercise Behavior and BMI - Osman İmamoğlu; Tülin Atan (Selcuk University, 2020)
The aim of this study is to investigate the personal nutritional habits of university students according to gender, BMI and exercise behavior stage. For this purpose, 348 female (age; 22.25±3.67 years) and 362 male (age; 22.49±3.28 years) students filled two questionnaires. First to determine the nutritional habits Personal Nutritional Assessment Questionnaire (PNAQ) was used. A total of 13 and below scores from the PNAQ are poor, 14-18 points are moderate, 19-23 points are good, and 24-25 points are excellent. Secondly, Exercise Stages of Change Questionnaire (ESCQ) was used to determine which stage of readiness the participants are currently in. The "stage based" handouts define the level of readiness and provide useful information on how to increase the amount of physical activity in life. Independent t-test, one way variance analysis and LSD tests were used in statistical analysis. The PNAQ's total nutritional score was found to be 16.26 in females and 16.17 in males, that is, moderate level. There was no statistically significant difference of the total nutritional scores according to gender (p gt;0.05) only a significant difference was found only in "milk" related sub-dimension, according to gender (p lt;0.001). Nutrition scores according to BMI did not differ in the sub-dimension of "meat or alternative nutrition", while nutrition scores in other categories differed statistically according to BMI (p lt;0.001). According to the stage of exercise behavior, the nutritional scores of students who are at the stage of pre-contemplation, contemplation and preparation are significantly lower than those in the stage of action and maintenance (p lt;0.001). As a result, nutrition levels of university students do not change much according to gender, but differ according to the BMI and to the stage of exercise behavior. The level of nutrition is moderate in those who are physically inactive and good in those who are active. Certain changes should be made in the diet of university students. It is thought that they should be educated about nutrition education, changing their eating habits, doing sports and being fit.